KEANEKARAGAMAN JENIS BAMBU DI DESA SARANG BURUNG KOLAM KECAMATAN JAWAI KABUPATEN SAMBAS - Jaidan, Jaidan; Wardenaar, Evy; Tavita, Gusti Eva (Universitas Tanjungpura, 2020)
Indonesia has 176 species of bamboo which constribute 16% of the world's bamboo species. 60% of bamboo grown in Indonesia is endemic bamboo. The purpose of this study was to record the diversity of bamboo species found in the Sarang Burung Kolam Village, Jawai District, Sambas Regency. The method used double plots laid out according to the presence of growing bamboo roaming with an observation plot area of 20 mx 20 m. Two different genera namely the genus Gigantochloa and Bambusa. Genus Bambusa consists of Bambusa vulgaris Schrad. Ex wendl, Bambusa vulgaris var. striata and Bambusa multiplex, Genus Gigantochloa consists of Gigantochloa balui and Gigantochloa atter). Type of bamboo that has the highest INP value is B. vulgaris Schrad. Ex wendl. (114.4599%,) the medium INP value is G. atter (55.4006%) and the lowest INP is B. vulgaris var.striata (3.2603%). Species Diversity Index in Desa Sarang Burung Kolam, Jawai District, Sambas Regency is relatively low.Keyword : Bamboo diversity, Sambas Regency, Sarang Burung Kolam Village